Pathogenicity tests of Gremmeniella abietina var. balsamea isolated from balsam fir in Canada - Smerlis †, Edgar; Laflamme, Gaston (Phytoprotection, 2010)
The pathogenicity of Gremmeniella abietina var. balsamea isolated from balsam fir (Abies balsamea) was tested on different conifer hosts, including A. balsamea. Pathogenicity of the fungus was positive on balsam fir only. This pathogen could not infect other conifers, not even spruce species which are reported as hosts for the taxon G. abietina var. balsamea. Also, isolates from spruces and pines were pathogenic only on their respective hosts. These results raise questions on the taxonomic status of the two pathogens classified as G. abietina var. balsamea.